Liver- and Colon-Specific DNA Methylation Markers in Plasma for Investigation of Colorectal Cancers with or without Liver Metastases. (1st August 2018) - Gai, Wanxia; Ji, Lu; Lam, W K Jacky; Sun, Kun; Jiang, Peiyong; Chan, Anthony W H; Wong, John; Lai, Paul B S; Ng, Simon S M; Ma, Brigette B Y; Wong, Grace L H; Wong, Vincent W S; et al.
Abstract: BACKGROUND: Measurement of DNA derived from different tissues in the circulating DNA pool can provide important information regarding the presence of many pathological conditions. However, existing methods involving genome-wide bisulfite sequencing are relatively expensive and may present challenges for large-scale analysis. METHODS: Through identifying differentially methylated regions in the liver and colon compared with other tissues, we identified 2 markers and developed corresponding droplet digital PCR assays. Plasma concentrations of liver-derived and colon-derived DNA were measured for 13 liver transplant recipients, 40 liver cancer patients, and 62 colorectal cancer (CRC) patients (27 with and 35 without liver metastases). RESULTS: In liver transplant recipients, the fractional concentration of liver-derived DNA measured using the liver-specific methylation marker and donor-specific alleles showed good correlation (Pearson R = 0.99). In liver cancer patients, the concentration of liver-derived DNA correlated positively with the maximal dimension of the tumor (Spearman R = 0.74). In CRC patients with and without liver metastasis, the plasma concentrations of colon-derived DNA (median, 138 copies/mL and 4 copies/mL, respectively) were increased compared with the 30 healthy controls (26 had undetectable concentrations). The absolute concentration of liver-derived DNA provided a better differentiation between CRC patients with and without liver metastasis compared with the fractional concentration (area under ROC curve, 0.85 vs 0.75). CONCLUSIONS: Quantitative analysis of plasma DNA with tissue-specific methylation patterns using droplet digital PCR is applicable for the investigation of cancers and assessing organ transplantation. This approach is useful for differentiating patients with and without metastases to other organs.